2003
DOI: 10.1136/bjo.87.10.1252
|View full text |Cite
|
Sign up to set email alerts
|

A two centre study of the dose-response relation for transscleral diode laser cyclophotocoagulation in refractory glaucoma

Abstract: Background/aims: Transscleral diode laser cyclophotocoagulation (''cyclodiode'') is widely used to treat refractory glaucoma. The main aims of this study were to investigate the dose-response relation of cyclodiode and to evaluate possible predictive factors that would help establish optimum treatment parameters. Methods: A retrospective analysis of the case notes of 263 eyes of 238 consecutive patients who underwent transscleral diode laser cyclophotocoagulation at two centres was undertaken. Results: Mean in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
121
3
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(140 citation statements)
references
References 17 publications
(22 reference statements)
12
121
3
4
Order By: Relevance
“…Murphy et al, 19 in their study on Caucasian eyes reported results similar to our study, but with higher energy levels. The mean laser energy delivered was 104.1737.5 J per session.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Murphy et al, 19 in their study on Caucasian eyes reported results similar to our study, but with higher energy levels. The mean laser energy delivered was 104.1737.5 J per session.…”
Section: Discussionsupporting
confidence: 90%
“…Reported success rates vary from 66 to 80% in Caucasians 15,18,19 to 92% in Indian eyes. 20 Taking a mean reported success rate of 70% and a difference of at least 20% to be significant, a study with 80% power and 5% significance would require a minimum of 63 patients, by the following formula:…”
Section: Sample Size Calculationmentioning
confidence: 99%
See 3 more Smart Citations